(untitled) (International journal of artificial intelligence, 2025)
Jack London, one of the most influential writers of the early 20th century, was a committed socialist whose literary works often explored themes of class struggle and social inequality. His novels and essays provide a critical examination of the capitalist system and advocate for the rights of the working class. This article explores the socialist ideas embedded in London’s writings, focusing on his major works such as The Iron Heel, The People of the Abyss, and Martin Eden. It examines how his personal experiences, political beliefs, and observations of social injustice shaped his literary output. By analyzing these works, we can better understand London’s vision of a society shaped by economic and social conflicts, as well as his contribution to socialist thought in literature.